Impact of blockchain technology adoption in farms of FPO members - S, NANDHINI; S D, SIVAKUMAR; PARASURAMAN, BALAJI; N, VENKATESA PALANICHAMY; V, ANANDHI; P, BALASUBRAMANIAN; R, VASANTHI; KUMAR, AJAY (The Indian Journal of Agricultural Sciences, 2023)
BCT adoption remains to be a promising way to achieve food security and safety in many developing countries. This paper explores the impact of blockchain technology adoption on household farm income. Based on a simple random sampling method, a cross sectional survey was conducted in the year 2023 to collect data from 240 sample farmers including 120 BCT adopters and 120 non-adopters in Erode district of Tamil Nadu. The information regarding socio-economic profiles like age, gender, educational status, farming experience, farm size, extension agency contact, training programmes attended, access to technological information were collected from sample farmers through personal interviews. The present research used a treatment effect analysis with propensity score matching approach to assess the impact of blockchain technology adoption on household’s farm income. Results showed a significant increase in farm income as a result of blockchain technology adoption among sample farmers. PSM approach estimated that the blockchain technology adopters earned higher farm income of ₹25829.16 as compared to non-adopters. Hence the findings provide empirical evidence that blockchain technology adoption in agriculture can contribute to improve quality food production and enhance farm income.